Earnings management, corporate social responsibility and corporate governance in Indonesian banking industry - Supardi Supardi; Yudi Santara Setyapurnama (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2020)
Abstract This paper describes the research which investigates the moderating effect of corporate governance (CG) on the relationship of earnings management (EM) practices and corporate social responsibility (CSR) disclosure in companies listed on the Indonesia Stock Exchange. EM used in this study is the different between discretionary realized security gain or loss and discretionary loan loss provition. Data is obtained by purposive sampling process with a total sample of 138 out of 46 banking sector companies. The results showed that EM had not effect on CSR and audit committee has a negative effect on CSR, but independent commissioner does not affect CSR if tested together with EM.